The influence of the open society theory on the socio-cultural aspects of modern education: some reflections - Azamatova, Gulrukh (MMIT Proceedings, 2024)
In this article, the author examines the influence of the open society theory on the socio-cultural aspects of modern education. By exploring the specifics of this influence, the author indicates how precisely the open society theory can transform contemporary education, while also highlighting critical points. The author concludes that despite some negative aspects of the open society theory, it plays a crucial role in the progressive development of educational systems.